“'Em meses de inverneira, histórias à lareira”. Provérbios e dizeres enquanto transmissores de valores culturais e de identidade - Hermínia Sol (Carnets)
Oral tradition is still looked down upon by academia as it is not yet considered fit to be either object or subject of scientific scrutiny. In an attempt to change this state of affairs, this article aims to reflect upon the role of proverbs and sayings as keepers of cultural and national values. As such, it will look into the didactic nature of these two communicational phenomena as a commitment to the cultures that have produced them. Borrowing from Durkheim and Vasina, it will explore the contribution of this kind of anonymous productions to the creation and maintenance of a community’s collective memory. Next it will draw some parallels between Portuguese national proverbs and some European equivalents, so as to attest their ancient role as vehicles for the exchange of ideas. Finally, especial attention will be given to some recent projects, which aim to protect and pass on certain aspects of our heritage through oral tradition.